2020
DOI: 10.20525/ijrbs.v9i6.919
|View full text |Cite
|
Sign up to set email alerts
|

Auditors’ professional commitment, time budget pressure, independence, and audit quality

Abstract: This study aims to investigate the effect of auditors’ professional commitment and audit time budget pressure on audit quality mediated by auditors’ independence at the Republic of Indonesia Supreme Audit Agency (BPK RI). This study applies explanatory research with a questionnaire method. The survey was conducted in mid-2020. The questionnaire was distributed to the head office and representative offices of BPK RI in 34 provinces. The samples of this study were 132 auditors of BPK RI throughout Indonesia. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In the literature, there are several studies focusing on the relationship between professional commitment, technostress, organizational stress, individual work performance, and independent audit quality (Doğrular, 2019;Günlük et al, 2017;Olasanmi, 2016;Hung et al, 2015;Tarafdar et al, 2015;Kumar et al, 2017;Yener, 2018;Lestari et al, 2020;Sunyoto, 2020). However, although the mediating role of professional commitment in the relationship between audit quality and individual work performance has been examined, to the best of our knowledge, no study yet tested the mediating role of professional commitment in the relationship between technostress and organizational stress, individual work performance, and independent audit quality.…”
Section: Theoretical Framework Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, there are several studies focusing on the relationship between professional commitment, technostress, organizational stress, individual work performance, and independent audit quality (Doğrular, 2019;Günlük et al, 2017;Olasanmi, 2016;Hung et al, 2015;Tarafdar et al, 2015;Kumar et al, 2017;Yener, 2018;Lestari et al, 2020;Sunyoto, 2020). However, although the mediating role of professional commitment in the relationship between audit quality and individual work performance has been examined, to the best of our knowledge, no study yet tested the mediating role of professional commitment in the relationship between technostress and organizational stress, individual work performance, and independent audit quality.…”
Section: Theoretical Framework Of the Studymentioning
confidence: 99%
“…In this context, studies examining the effect of professional commitment on the quality of independent auditing revealed that the quality of independent auditing increases as the level of professional commitment of independent auditors increases (Selimoğlu & Yeşilçelebi, 2014;Tandiontong, 2013). There are studies in the literature that found professional commitment has a positive relationship with audit quality (Lestari et al, 2020;Leo Handoko et al, 2021). Thus, the hypothesis was generated as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research also shows that time pressure is causing work-stress and interrupt the independence to work on the audit procedure and therefore it has a positive impact on the audit quality (Amalia et al, 2019) Commitments are mentioned during the interview with all of the respondents, it means, commitment is the key to ease the problem of time pressure. Professional commitment (Lestari et al, 2020) also gives a positive impact on audit quality. Thus, the time pressure has a huge impact on the audit quality of BPR ABC and this is in line with the research by Kirana (2020).…”
Section: Mrs Nandamentioning
confidence: 99%
“…During the pandemic, the time budget also got reduced to decrease mobility and part of the virus prevention. Audit time budget is the time limit for the auditors to complete their audit work at a specified time (Lestari et al, 2020). The existence of time pressure can affect audit quality, where it is based on assumption that related to the audit pressure experienced by the company during the acceleration period, the presence of time pressure will cause difficulties in the audit process, so many companies try to ease the audit time pressure so that audit quality generated can be accelerated and can still provide accurate information to users of financial statements (Lambert et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Financial services, control, and corporate governance are evaluated and improved methodically and systematically to enable an organization to achieve its goals. Auditors are those who gather and analyse data to assess how well it complies with set criteria [6]. The establishment of formal systems of external control is a must for any effective accounting system.…”
Section: Introductionmentioning
confidence: 99%